1957
DOI: 10.1139/p57-024
|View full text |Cite
|
Sign up to set email alerts
|

Emission Band Spectra of Nitrogen: A Study of Some Singlet Systems

Abstract: Ten bands of Gaydon's and Herman's singlet systems and eight new bands have been photographed under high resolution and analyzed in detail. Two of the new transitions were shown to be '22-a 'II,, the upper state being in one case identical with Watson's and ICoontz's state g, and one new transition to be ' Ao-w ' A, in type. I t is proposed that the new state 'A, has the same electron configuration as the x '2; state. Two bands in the red and one band in the ultraviolet could not be assigned with certainty. Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

1976
1976
2002
2002

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 8 publications
3
24
0
Order By: Relevance
“…40 Finally, the sixth identified singlet gerade state is the z 1 ⌬ g state. This state was observed by Lofthus in 1957 41 in emission. Although this is the only reported observation up to our knowledge, the state is also found in the ab initio calculations of Michels.…”
Section: Introductionsupporting
confidence: 63%
“…40 Finally, the sixth identified singlet gerade state is the z 1 ⌬ g state. This state was observed by Lofthus in 1957 41 in emission. Although this is the only reported observation up to our knowledge, the state is also found in the ab initio calculations of Michels.…”
Section: Introductionsupporting
confidence: 63%
“…Lofthus [423] observed a new band, degraded to longer wavelengths, at 2498. 6 A, the analysis of which showed that it was due to a transition from an upper level tI:u-l-to v=O of (LlII g • The pusitiu1l of the J. Phys.…”
Section: C~(4) =Hmentioning
confidence: 98%
“…by J anin (m, b' and d) and by J anin and Crozet [347], who added three new systems to this group (0, ~, and d"). Lofthus [423] remeasured most of the bands at higher resolution, and added two new transitions (g and k).…”
Section: C~(4) =Hmentioning
confidence: 99%
See 2 more Smart Citations